Solving large-scale support vector ordinal regression with asynchronous parallel coordinate descent algorithms. (January 2021) - Gu, Bin; Geng, Xiang; Shi, Wanli; Shan, Yingying; Huang, Yufang; Wang, Zhijie; Zheng, Guansheng
Highlights: We highlight a special SVOR formulation whose thresholds are described implicitly, so that the dual formulation is concise to apply the state-of-the-art asynchronous parallel coordinate descent algorithm, such as AsyGCD. We propose two novel asynchronous parallel coordinate descent algorithms, called AsyACGD and AsyORGCD respectively. AsyACGD is an accelerated extension of AsyGCD using active set strategy. AsyORGCD is specifically designed for SVOR that it can keep the ordered thresholds when it is training so that it can obtain good performance with fewer time. Abstract: Ordinal regression is one of the most influential tasks of supervised learning. Support vector ordinal regression (SVOR) is an appealing method to tackle ordinal regression problems. However, due to the complexity in the formulation of SVOR and the high cost of kernel computation, traditional SVOR solvers are inefficient for large-scale training. To address this problem, in this paper, we first highlight a special SVOR formulation whose thresholds are described implicitly, so that the dual formulation is concise to apply the state-of-the-art asynchronous parallel coordinate descent algorithm, such as AsyGCD. To further accelerate the training for SVOR, we propose two novel asynchronous parallel coordinate descent algorithms, called AsyACGD and AsyORGCD respectively. AsyACGD is an accelerated extension of AsyGCD using active set strategy. AsyORGCD is specifically designed for SVOR that it can keep the ordered thresholds when it is training so that it can obtain good performance with lower time. Experimental results on several large-scale ordinal regression datasets demonstrate the superiority of our proposed algorithms.